The promotion of well‐being among children exposed to intimate partner violence: a systematic review of interventions - Latzman, Natasha E. (Campbell Systematic Reviews, 2019)
Exposure to IPV childhood can have both short- and long-term negative impacts to health and well-being that persist across generations. There is therefore an increased interest in the development of intervention strategies to promote well-being following exposure. Over the last two decades, theory-driven psychosocial programs serving children exposed to violence have been developed and established in a range of venues (e.g., school-based mental health clinics, outpatient psychotherapy settings). This review provides a synthesis of the state of this literature and implications for research and practice.